PARADIGMA POLITISASI AGAMA: UPAYA REPOSISI AGAMA DALAM WILAYAH PUBLIK - Ruslan, Idrus (Madania: Jurnal Kajian Keislaman, 2014)
Paradigm Deconstruction of Politicized Religion: An Efort to Re-position Religion in Public Area. Religionis often used as a political “commodity” by many candidates of chief executive and legislative leader throughusing jargons, slogans, issues in accordance with the term of religion as well as religious nuance. It can befound when the general or regional election will be undertaken soon. The behavior can be analyzed throughthe dramaturgi theory introduced by Erving Gofmann and identity manipulation theory stated by Amstrong.The behavior is also considered as a common legel when it is manifested in real, empiric, and factual life- andalso applied responsibility. It is because the moral and religious values are not only as accessory but also assomething should be applied in real daily life. Of course, the out of such expected matter is hypocrite